Perilaku pengomposan rumah tangga sampah makanan pada Perumahan Batan Indah dan Kelurahan Lengkong Gudang, Tangerang Selatan - Rohadatul Aisy Afla; Dwi Nowo Martono; Sri Wahyono (Jurnal Penelitian Pendidikan IPA, 2023)
The high burden of final waste management causes pollution due to the low contribution of prevention at the source. The composition of Indonesia's food waste reaches 40.62%. Proper food waste management has become a challenge because the habit of segregation at the household level is still low. Home-composting is an option for management from sources with technology that is easy to operate, but its use still needs to be improved. This study looks at the factors influencing people's behaviour in composting-based household food waste management. The objective of this study is to analyze the variables of attitudes, subjective norms, and behavioural control, which affect behaviour in home-composting activities, using the theory of planned behaviour model. A quantitative approache with multiple regression analysis was used in the study. Subjective norms and behavioural control significantly (p < 0.05) influence home-composting behaviour, while attitudes (p > 0.05) do not influence home-composting.